'He should have put them in the freezer': Creating and connecting through shared reading. (1st September 2015) - Jones, Susan; Harvey, Kevin
Shared reading involves reading short stories, poems, novels and plays aloud with groups of people who meet in a range of settings. Readings are conducted by a facilitator, after which the group members share their responses to the texts. The social and therapeutic benefits of shared reading have been well-documented, often with an emphasis on the role of literature in improving the well-being of individuals. In this article, we bring together our backgrounds in the study of sociolinguistics and literacy education to discuss the work of an inner city shared reading group with which we are both involved. The emphasis in the shared reading we present is on the members' active and agentive participation in the co-construction of meaning through shared reading and the discussion of texts. We argue that a focus on the collaborative aspect of shared reading contributes to understanding of the role it can play in supporting inclusive, participatory arts practice in communities.